Chronic intermittent ethanol exposure during adolescence: effects on social behavior and ethanol sensitivity in adulthood - Varlinskaya, Elena I. (2014)
This study assessed long-lasting consequences of repeated ethanol exposure during two different periods of adolescence on 1) baseline levels of social investigation, play fighting, and social preference and 2) sensitivity to the social consequences of acute ethanol challenge. Adult male and female Sprague-Dawley rats were tested 25 days after repeated exposure to ethanol (3.5 g/kg intragastrically [i.g.], every other day for a total of 11 exposures) in a modified social interaction test. Early-mid adolescent intermittent exposure (e-AIE) occurred between postnatal days (P) 25–45, whereas late adolescent intermittent exposure (l-AIE) was conducted between P45–65. Significant decreases in social investigation and social preference were evident in adult male rats, but not their female counterparts following e-AIE, whereas neither males nor females demonstrated these alterations following l-AIE. In contrast, both e-AIE and l-AIE produced alterations in sensitivity to acute ethanol challenge in males tested 25 days after adolescent exposure. Ethanol-induced facilitation of social investigation and play fighting, reminiscent of that normally seen during adolescence, was evident in adult males after e-AIE, whereas control males showed an age-typical inhibition of social behavior. Males after l-AIE were found to be insensitive to the socially suppressing effects of acute ethanol challenge, suggesting the development of chronic tolerance in these animals. In contrast, females showed little evidence for alterations in sensitivity to acute ethanol challenge following either early or late AIE. The results of the present study demonstrate a particular vulnerability of young adolescent males to long-lasting detrimental effects of repeated ethanol. Retention of adolescent-typical sensitivity to the socially facilitating effects of ethanol could potentially make ethanol especially appealing to these males, therefore promoting relatively high levels of ethanol intake later in life.